Renewable and reusable heavy metal ion solid precipitant and preparation method thereof
By hydrolysis and copolymerization on polyacrylonitrile powder, combined with crosslinking and oximeification reaction, a solid particle-formed amidoxime type precipitant with high-efficiency heavy metal ion adsorption ability was prepared, solving the efficiency and sustainability of existing precipitants when treating low-concentration heavy metal wastewater, and achieving efficient and reusable heavy metal ions removal and recovery.
Patent Information
- Application Number
- CN202510126771.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-27
- Publication Date
- 2025-06-13
AI Technical Summary
When treating low-concentration heavy metal wastewater, existing heavy metal ion precipitants have problems such as large doses of disposal, difficulty in post-treatment, and poor effect on complexing agent-containing wastewater. Moreover, the amidoxime type precipitants are prone to agglomeration, poor rigidity and low adsorption performance, and are difficult to apply on a large scale.
Polyacrylonitrile powder is prepared by hydrolysis of alkaline solution or copolymerization of acrylonitrile and acrylic acid. The amidoxime type precipitant in solid particles is formed by cross-linking and oxime-forming reaction, which has a cross-linked network structure and efficient heavy metal ion adsorption ability.
It has achieved efficient adsorption of heavy metal ions such as copper and nickel, and has the characteristics of fast adsorption speed, large adsorption capacity, high strength, easy separation and reusable. It is suitable for heavy metal recycling in the fields of hydrometallurgy, environmental protection and mining.
Smart Images

Figure CN120137080A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a renewable and reusable heavy metal ion solid precipitant and a preparation method thereof. The precipitant is particularly applicable to the recovery and treatment of heavy metals such as copper in the fields of hydrometallurgy and environmental protection, as well as the recovery of low-concentration gold in gold mines and low-concentration uranium in uranium mines, and belongs to the technical field of heavy metal wastewater treatment. Background Art
[0002] Heavy metal wastewater is generated in the fields of hydrometallurgy, electroplating, chemical engineering and other environmental protection fields. Among them, the discharge of heavy metals such as low-concentration copper, cadmium, lead, and chromium will cause harm to the environment and human health through the accumulation of the food chain, and at the same time will cause waste of resources. Therefore, how to achieve zero discharge of low-concentration heavy metals and resource recovery of high-concentration heavy metals is the focus of work in the environmental protection field. In addition, in mining fields such as gold mines and uranium mines, there are problems such as difficulty in recovering low-concentration precious metal mineral resources.
[0003] Heavy metal ion precipitants are one of the most widely used materials in the current industrial treatment of heavy metal wastewater. Currently, the mainly used ones are neutralization precipitants and sulfide precipitants, etc., which have the disadvantages of large dosage, difficult post-treatment and poor effect on wastewater containing complexing agents. The amidoxime-type precipitant is generally obtained by directly carrying out amidoximation modification on polyacrylonitrile powder, but this method has the disadvantages of easy agglomeration, poor rigidity and low adsorption performance, so it is difficult to be applied on a large scale. Summary of the Invention
[0004] In order to overcome the defects existing in the prior art, the purpose of the present invention is to provide a renewable and reusable heavy metal ion solid precipitant and a preparation method thereof; the precipitant is particularly applicable to the removal and recovery of precious metals and heavy metals in the fields of environmental protection, mining and hydrometallurgy.
[0005] In order to achieve the purpose of the present invention, the following technical solutions are provided.
[0006] A renewable and reusable heavy metal ion solid precipitant, and the structural formula of the precipitant is as follows:
[0007]
[0008] Among them, the value of n is 70-700.
[0009] The precipitant is an amidoxime-type precipitant in the form of solid particles and has a cross-linked network structure.
[0010] A preparation method of the renewable and reusable heavy metal ion solid precipitant of the present invention, and the method steps are as follows:
[0011] (1) The hydrolysis product is prepared by hydrolyzing polyacrylonitrile powder with an alkaline solution. After washing, filtering and drying, product A is obtained;
[0012] Or the polymerization product is prepared by copolymerizing acrylonitrile and acrylic acid. After washing, filtering and drying, product A is prepared;
[0013] Product A is a powder with carboxylic acid groups on its surface. The content of carboxylic acid groups in product A is 0.5 mmol / g to 2 mmol / g, and the density of product A is 1.0 g / cm 3 ~1.2 g / cm 3 .
[0014] In the method of hydrolyzing polyacrylonitrile powder with an alkaline solution:
[0015] The molecular weight of the polyacrylonitrile powder is 3000 to 30000, and the hydrolysis reaction temperature is 50 °C to 90 °C;
[0016] Preferably, the hydrolysis reaction time of the alkaline solution is 0.5 h to 2 h;
[0017] Preferably, the alkaline solution is a solution of at least one alkaline substance among sodium hydroxide, potassium hydroxide, sodium carbonate and guanidine carbonate; further, more preferably, the mass fraction of the alkaline substance in the alkaline solution is 1% to 8%; more preferably, the alkaline solution is a sodium hydroxide solution.
[0018] In the method of copolymerizing acrylonitrile and acrylic acid:
[0019] Preferably, based on the total mass of acrylonitrile and acrylic acid being 100%, the mass fraction of acrylic acid is 1% to 10%.
[0020] Preferably, the hydrolysis product is prepared by hydrolyzing polyacrylonitrile powder with an alkaline solution. After washing, filtering and drying, product A is obtained.
[0021] (2) The product A prepared in step (1) is subjected to a crosslinking and curing reaction with an amine-containing crosslinking agent solution. After washing, filtering and drying the cured product, product B is obtained;
[0022] Preferably, the amine-containing crosslinking agent is at least one of polyethyleneimine, polyvinylamine, polyethylenepolyamine and triethylenetetramine; further, based on the total mass of the amine-containing crosslinking agent solution being 100%, the mass fraction of the amine-containing crosslinking agent is 1% to 10%; more preferably, the amine-containing crosslinking agent is triethylenetetramine;
[0023] Preferably, the amine groups in the amine-containing crosslinking agent are in excess relative to the carboxylic acid groups in product A;
[0024] Preferably, the reaction temperature for crosslinking and curing is 70 °C to 100 °C, and the reaction time is 2 h to 6 h.
[0025] (3) React the product B prepared in step (2) with a hydroxylamine reagent solution to carry out an oximation reaction, so that the amino group reacts to become amidoxime. After the reaction product is washed, filtered and dried, a renewable and reusable heavy metal ion solid precipitant is obtained.
[0026] The pH value of the hydroxylamine reagent solution is 6 - 7.
[0027] Preferably, the hydroxylamine reagent is hydroxylamine hydrochloride or hydroxylamine sulfate, and more preferably, the hydroxylamine reagent is hydroxylamine hydrochloride.
[0028] Preferably, the mass of the hydroxylamine reagent is 0.5 - 2 times the mass of product B.
[0029] Preferably, the temperature of the oximation reaction is 70°C - 90°C, and the reaction time is 0.5 h - 4 h.
[0030] Regarding the use of the renewable and reusable heavy metal ion solid precipitant of the present invention, the precipitant can be used for the removal and recovery of heavy metal ions; in particular, it is suitable for the removal and recovery of copper ions or nickel ions.
[0031] Beneficial effects
[0032] (1) The present invention provides a renewable and reusable heavy metal ion solid precipitant. The precipitant is an amidoxime-type precipitant in the form of solid particles, which has a cross-linked network structure. The amidoxime groups on the surface can undergo chelation and coordination reactions with heavy metal ions such as copper and nickel; the precipitant has the characteristics of fast adsorption speed, large adsorption capacity, high strength, easy separation and recyclability.
[0033] (2) The present invention provides a preparation method of a renewable and reusable heavy metal ion solid precipitant. The method mainly prepares an amidoxime-type heavy metal precipitant by a grafting method, and creatively introduces a cross-linking process before the grafting reaction. The cross-linking reaction can make the particle size of the precipitant particles larger and the density increase, which not only enhances the self-strength of the precipitant and avoids fragmentation during application, but also facilitates subsequent separation treatment.
[0034] (3) The present invention provides a preparation method of a renewable and reusable heavy metal ion solid precipitant. In the method, the oximation reaction occurs on the outer surface of the matrix, so that the functional groups are all exposed on the outer layer, reducing the attack reaction of chemical reagents on the inside of the matrix. This not only ensures that the self-strength of the precipitant is not damaged, but also enhances its binding speed with heavy metal ions.
[0035] (4) The present invention provides a preparation method of a renewable and reusable heavy metal ion solid precipitant. In step (1) of the method, product A can be obtained by two methods. One is using polyacrylonitrile powder as the matrix, and the nitrile group is partially hydrolyzed into carboxyl groups, so that the surface contains carboxyl groups after hydrolysis; the other method is to directly polymerize acrylonitrile and acrylic acid to obtain a powder matrix containing carboxyl groups. Both methods are used to obtain a polyacrylonitrile powder matrix with carboxyl groups on the surface.
[0036] (5) The present invention provides a preparation method of a renewable and reusable heavy metal ion solid precipitant. During the use of this method, no hazardous waste is generated, no additional flocculant needs to be added, etc., and the purity of the precipitated product is high.
[0037] (6) The present invention provides a preparation method of a renewable and reusable heavy metal ion solid precipitant. The method is simple and easy for industrial production, and is especially suitable for the removal and recovery of precious and heavy metals in hydrometallurgy, environmental protection, mining, etc., and can also be used for the recovery of uranium in uranium mines. Detailed implementation mode
[0038] The present invention will be described in detail below with specific examples, but it does not limit the scope of the invention patent.
[0039] Example 1
[0040] (1) Add polyacrylonitrile powder with a molecular weight of 3000 to a sodium hydroxide solution with a mass fraction of 1%, carry out hydrolysis reaction at 50 °C for 0.5 h, wash and filter the obtained hydrolysis product, and dry it in a vacuum oven at 95 °C for 2 h to obtain product A;
[0041] Product A is a powder with carboxylic acid groups on the surface. By using the acid-base neutralization titration method, the content of carboxylic acid groups is measured to be 0.5 mmol / g, and the density of product A is 1.0 g / cm 3 .
[0042] (2) Add 1 g of product A prepared in step (1) to 100 ml of a polyethylenepolyamine solution with a mass fraction of 1%, carry out cross-linking and curing reaction at 70 °C for 2 h, and after washing, filtering and drying the cured product, obtain product B.
[0043] (3) Dissolve 0.5 g of hydroxylamine hydrochloride in 100 ml of water, adjust the pH value of the solution to 6 with 0.1 mol / L sodium carbonate solution to prepare a hydroxylamine hydrochloride solution; add 1 g of product B to the hydroxylamine hydrochloride solution, carry out oximation reaction at 70 °C for 0.5 h, and after washing, filtering and drying the reaction product, obtain the final product in the form of solid particles, which is a renewable and reusable heavy metal ion solid precipitant.
[0044] The final product prepared in this example was tested as follows:
[0045] (1) Infrared spectrum test
[0046] At 3300cm -1 ~3500cm -1 There are absorption peaks in the region, which are manifested as multiple medium-intensity absorption peaks. The amine group (-NH 2 ) can be used as a preliminary basis for judging the existence of amidoxime groups.
[0047] At 1650cm -1 ~1690cm -1 A strong absorption peak appears in the region, which is the stretching vibration of the C=N double bond in the amidoxime group.
[0048] At 1200cm -1 ~1300cm -1 There is an absorption peak in the region with medium intensity, which is the stretching vibration of the NO bond in the amidoxime group;
[0049] According to the above test results and the fact that the raw material used is polyacrylonitrile powder with a molecular weight of 3000, it can be known that the structural formula of the final product is as follows:
[0050]
[0051] Wherein, the value of n is 70, which is a renewable and reusable heavy metal ion solid precipitant described in the present invention.
[0052] (2) Copper ion adsorption performance test
[0053] Weigh 0.1 g of the final product and put it into 20 ml of copper nitrate solution with an initial copper ion concentration of 1000 mg / L. Adjust the pH value of the solution to 5 with 0.1 mol / L hydrochloric acid solution. Adsorb for 15 minutes in a constant temperature oscillation box at a speed of 100 rpm and 25°C. Test the concentration of the copper nitrate solution after adsorption with an atomic absorption spectrophotometer. It can be seen that the adsorption amount of copper by the final product is 75.5 mg / g. It is a solid precipitant that can adsorb copper ions.
[0054] (3) Recycling and reuse test
[0055] The final product after copper adsorption was eluted with 0.1 mol / L hydrochloric acid solution for 10 min, then washed with pure water for 4 times, then immersed in 0.1 mol / L sodium hydroxide for 10 min, and then washed with pure water until neutral. (2) The copper ion adsorption performance test was carried out. The test results showed that the recycled product had an adsorption capacity of 75.2 mg / g for copper. Therefore, it can be known that the final product is a renewable and reusable heavy metal ion solid precipitant.
[0056] Example 2
[0057] (1) Polyacrylonitrile powder with a molecular weight of 30,000 was added to a 8% guanidine carbonate solution, and hydrolysis reaction was carried out at 90 °C for 2 h. The obtained hydrolysis product was washed and filtered, and then dried in a vacuum oven at 95 °C for 2 h to obtain product A;
[0058] Product A is a powder with carboxylic acid groups on its surface. By using acid-base neutralization titration method, the content of carboxylic acid groups was measured to be 2 mmol / g, and the density of product A is 1.2 g / cm 3 .
[0059] (2) 1 g of product A prepared in step (1) was added to 100 ml of a 10% triethylenetetramine solution, and cross-linking and curing reaction was carried out at 100 °C for 6 h. After the cured product was washed, filtered and dried, product B was obtained.
[0060] (3) 2 g of hydroxylamine sulfate was dissolved in 100 ml of water, and the pH value of the solution was adjusted to 7 with 0.1 mol / L sodium carbonate solution to prepare a hydroxylamine sulfate solution; 1 g of product B was added to the hydroxylamine sulfate solution, and oximation reaction was carried out at 90 °C for 4 h. After the reaction product was washed, filtered and dried, the final product in the form of solid particles, a renewable and reusable heavy metal ion solid precipitant, was obtained.
[0061] The final product prepared in this example was tested as follows:
[0062] (1) Infrared spectrum test
[0063] The test results showed that there were absorption peaks in the range of 3300 cm -1 ~3500 cm -1 region, showing multiple medium-intensity absorption peaks, which were the stretching vibrations of the N-H bond in the amino group (-NH 2 ) in the amidoxime group, and could be used as a preliminary judgment basis for the existence of the amidoxime group.
[0064] There was a strong absorption peak in the range of 1650 cm -1 ~1690 cm -1 region, which was the stretching vibration of the C=N double bond in the amidoxime group.
[0065] There was an absorption peak in the range of 1200 cm -1 ~1300 cm -1 region with medium intensity, which was the stretching vibration of the N-O bond in the amidoxime group;
[0066] According to the above detection results and the raw material used was polyacrylonitrile powder with a molecular weight of 30,000, the structural formula of the final product was as follows:
[0067]
[0068] Among them, the value of n is 700, which is a kind of heavy metal ion solid precipitant that can be regenerated and reused according to the present invention.
[0069] (2) Performance test for nickel ion adsorption:
[0070] Weigh 0.1 g of the final product and put it into 20 ml of nickel nitrate solution with an initial nickel ion concentration of 1000 mg / L. Adjust the pH value of the solution to 4.5 with 0.1 mol / L hydrochloric acid solution, and adsorb it in a constant temperature shaker at a rotation speed of 100 r / min and 25 °C for 15 min. Measure the concentration of the nickel nitrate solution after adsorption by an atomic absorption spectrophotometer. It can be known that the adsorption capacity of nickel by the final product is 68.5 mg / g, and it is a solid precipitant that can adsorb copper ions.
[0071] (3) Regeneration and reuse test
[0072] Elute the final product after nickel adsorption with 0.1 mol / L hydrochloric acid for 10 min, and then activate it with 0.1 mol / L sodium hydroxide for 10 min. Conduct the performance test for nickel ion adsorption in (2). The test shows that the adsorption capacity of nickel by the reused product is 68.0 mg / g. Therefore, it can be known that the final product is a kind of heavy metal ion solid precipitant that can be regenerated and reused.
Claims
1. A renewable and reusable heavy metal ion solid precipitant, characterized in that: The structural formula of the precipitant is as follows: Among them, the value of n is 70~700.
2. The renewable and reusable heavy metal ion solid precipitant according to claim 1, characterized in that: The precipitant is an amidoxime-type precipitant in the form of solid particles and has a cross-linked network structure.
3. A method for preparing a renewable and reusable heavy metal ion solid precipitant as claimed in claim 1 or 2, characterized in that: (1) using polyacrylonitrile powder with a molecular weight of 3000 to 30000, and preparing a hydrolysis product by hydrolysis with an alkaline solution, wherein the hydrolysis reaction temperature is 50° C. to 90° C.; after washing, filtering and drying, a product A is obtained; Alternatively, a polymer product is prepared by copolymerizing acrylonitrile and acrylic acid, and after washing, filtering and drying, a product A is prepared; Product A is a powder with carboxylic acid groups on the surface, with a carboxylic acid group content of 0.5mmol / g to 2mmol / g and a density of 1.0g / cm 3 ~1.2g / cm 3 ; (2) subjecting product A to a crosslinking and curing reaction using an amine-containing crosslinking agent solution, and washing, filtering and drying the cured product to obtain product B; (3) The product B is subjected to an oximation reaction with a hydroxylamine reagent solution having a pH value of 6 to 7, and the reaction product is washed, filtered and dried to obtain a regenerable and reusable heavy metal ion solid precipitant.
4. The method for preparing a renewable and reusable heavy metal ion solid precipitant according to claim 3, characterized in that: In step (1): In the method of hydrolyzing polyacrylonitrile powder with an alkaline solution, the alkaline solution is a solution of at least one alkaline substance selected from the group consisting of sodium hydroxide, potassium hydroxide, sodium carbonate and guanidine carbonate; In the method of copolymerizing acrylonitrile and acrylic acid, the mass fraction of acrylic acid is 1% to 10% based on the total mass of acrylonitrile and acrylic acid as 100%; In step (2): The amine-containing cross-linking agent is at least one of polyethyleneimine, polyethyleneamine, polyethylenepolyamine and triethylenetetramine; the amine groups in the amine-containing cross-linking agent are in excess relative to the carboxylic acid groups in the product A; In step (3): The hydroxylamine reagent is hydroxylamine hydrochloride or hydroxylamine sulfate.
5. The method for preparing a renewable and reusable heavy metal ion solid precipitant according to claim 4, characterized in that: In step (1): the mass fraction of the alkaline substance in the alkaline solution is 1% to 8%; In step (2): based on the total mass of the amine-containing cross-linking agent solution as 100%, the mass fraction of the amine-containing cross-linking agent is 1% to 10%; In step (3): the mass of the hydroxylamine reagent is 0.5 to 2 times the mass of the product B.
6. The method for preparing a renewable and reusable heavy metal ion solid precipitant according to claim 5, characterized in that: In step (1): the alkaline solution is a sodium hydroxide solution; In step (2): the amine-containing cross-linking agent is triethylenetetramine; In step (3): the hydroxylamine reagent is hydroxylamine hydrochloride.
7. A method for preparing a renewable and reusable heavy metal ion solid precipitant according to any one of claims 4 to 6, characterized in that: In step (1), the alkaline solution hydrolysis reaction time is 0.5h to 2h; In step (2), the reaction temperature of cross-linking curing is 70°C to 100°C, and the reaction time is 2h to 6h; In step (3), the temperature of the oximation reaction is 70°C to 90°C, and the reaction time is 0.5h to 4h.
8. A use of the renewable and reusable heavy metal ion solid precipitant as claimed in claim 1 or 2, characterized in that: The precipitant is used for removing and recovering heavy metal ions.
9. The use of a renewable and reusable heavy metal ion solid precipitant according to claim 8, characterized in that: The heavy metal ions are copper ions or nickel ions.